BUDAYA ENGAGEMENT: PENGARUHNYA TERHADAP KEUNGGULAN KOMPETITIF PADA SEKOLAH SWASTA DI SEMARANG - Pradana, Dominicus Wahyu (Universitas Dr. Soetomo, 2017)
This research aimsto analyze the influence of commitment, leadership, work environment and compensation to competitive advantages with engagement as intervening variable. Culture of engagement should be acquired by each employee in order to reach the competitive advantages.Samples were selected with census method or population research. Data are collected by distributing questionnaires to 35 senior high school teachers. Databe analyzed using Structural Equation Model (SEM) with PLS (Partial Least Squares) program.The result shows that 5 from 9 hypotheses argued are accepted, they are H2, H3, H6, H7 and H9. Research hypotheses include: the influence of leadership to engagement, the influence of work environment to engagement, the influence of leadership to competitive advantages, the influence of work environment to competitive advantages and the influence of engagement to competitive advantages.Whereas four other hypotheses (H1, H4, H5, H8) are rejected, they are the influence of commitment to engagement, the influence of commitment to competitive advantages, the influence of compensation to engagement, and the influence of compensation to competitive advantages. Keywords: commitment, leadership, work environment, compensation, engagement, competitive advantages.